(untitled) (Research, Society and Development, 2021)
This study aims to know the experience of women who had a home birth in the cities of São Luís, and São José de Ribamar, in the state of Maranhão. This is an exploratory, descriptive study with a qualitative approach, with the participation of 9 women and the interviews were carried out from September to October 2017. For the data analysis, we used the Bardin content analysis technique. From the results three thematic categories emerged. 1- Motivators for the experience of home birth; 2- The visions of the home birth; 3- Emmersion of feelings with the experience of home birth. The interviews showed that the desire for autonomy, respect, protagonism, high family income and education level were decisive points for the experience of home birth, as well as the support of prenatal consultations. Thus, it was possible to conclude that home delivery is nowadays a confrontation with what is offered by public or private health systems, emerging from a need to viscerally experience the physiology of the female body. The protagonism of this new birth choice evidenced the desire to feel active in their births.